2020
DOI: 10.1097/aln.0000000000003132
|View full text |Cite|
|
Sign up to set email alerts
|

Subomohyoid Anterior Suprascapular Block versus Interscalene Block for Arthroscopic Shoulder Surgery

Abstract: Background: Interscalene brachial plexus block, the pain relief standard for shoulder surgery, is an invasive technique associated with important complications. The subomohyoid anterior suprascapular block is a potential alternative, but evidence of its comparative analgesic effect is sparse. The authors tested the hypothesis that anterior suprascapular block is noninferior to interscalene block for improving pain control after shoulder surgery. As a secondary objective, the authors evaluated the success of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 57 publications
(78 reference statements)
0
31
1
Order By: Relevance
“…Our results are congruent with those of Auyong's recent study [21] comparing single-shot anterior SSB, supraclavicular, and interscalene blocks, which showed that anterior SSB provided non-inferior analgesia than interscalene and also preserved vital capacity. Similarly, Abdallah et al [22] also found that the anterior SSB was not inferior to the ISB for postoperative pain control. However, the analgesic effects of posterior SSB are inferior to those of ISB, with high pain scores at 6 and 12 hours on movement.…”
Section: Discussionmentioning
confidence: 83%
“…Our results are congruent with those of Auyong's recent study [21] comparing single-shot anterior SSB, supraclavicular, and interscalene blocks, which showed that anterior SSB provided non-inferior analgesia than interscalene and also preserved vital capacity. Similarly, Abdallah et al [22] also found that the anterior SSB was not inferior to the ISB for postoperative pain control. However, the analgesic effects of posterior SSB are inferior to those of ISB, with high pain scores at 6 and 12 hours on movement.…”
Section: Discussionmentioning
confidence: 83%
“…Because some articles did not compare the suprascapular nerve block with interscalene nerve block, five studies were excluded. Finally, we identified 1255 patients assessed in 17 randomized controlled trials [ 1 , 3 , 7 , 11 , 20 , 21 , 25 , 28 – 31 , 34 , 35 , 40 , 42 – 44 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have confirmed the efficacy of these two methods compared to control, intravenous patient-controlled analgesia (IV-PCA), and local anesthetic infiltration ( 5-7 , 11 , 16 ,). Although many studies have compared the analgesic efficacy of SSNB and ISNB ( 2 , 17 , 21 , 27 - 39 ), this is the first study to compare C-SSNB and S-ISNB with rebound pain at 6-12 h after surgery as a primary endpoint.…”
Section: Discussionmentioning
confidence: 99%